Inactivation of Cyclin-Dependent Kinase 5 in Hair Cells Causes Hearing Loss in Mice - Zhai, Xiaoyan; Liu, Chengcheng; Zhao, Bin; Wang, Yanfei; Xu, Zhigang (Frontiers in Molecular Neuroscience, 2018)
Cyclin-dependent kinase 5 (CDK5) is abundantly expressed in post-mitotic cells including neurons. It is involved in multiple cellular events, such as cytoskeletal dynamics, signaling cascades, gene expression, and cell survival, et al. Dysfunction of CDK5 has been associated with a number of neurological disorders. Here we show that CDK5 is expressed in mouse cochlear hair cells, and CDK5 inactivation in hair cells causes hearing loss in mice. CDK5 inactivation has no effect on stereocilia development in the cochlear hair cells. However, it affects stereocilia maintenance, resulting in stereocilia disorganization and eventually stereocilia loss. Consistently, hair cell loss was significantly elevated by CDK5 inactivation. Despite that CDK5 has been shown to play important roles in synapse development and/or function, CDK5 inactivation does not affect the formation of ribbon synapses of cochlear hair cells. Further investigation showed that CDK5 inactivation causes reduced phosphorylation of ERM (ezrin, radixin, and moesin) proteins, which might contribute to the stereocilia deficits. Taken together, our data suggest that CDK5 plays pivotal roles in auditory hair cells, and CDK5 inactivation causes hearing loss in mice.